"\\frac {n}{a_1 - a_0} + \\frac {n-1}{a_2-a_1} +\\cdots + \\frac {1}{a_n - a_n-1} \\geq \\sum_{k=1}^{n} \\frac {k^2}{a_k}"
After dividing both sides by right hand side
where
"\\sum_{k=1}^{n} \\frac {\\frac {n-1}{a_2 - a_1}}{\\frac {k^2}{a_k}}= \\frac {\\frac {n-1}{a_2 - a_1}}{\\frac {1^2}{a_1}} +\n \\frac {\\frac {n-1}{a_2 - a_1}}{\\frac {2^2}{a_2}} + \\dots + \\frac {\\frac {n-1}{a_2 - a_1}}{\\frac {n^2}{a_n}}"
"\\sum_{k=1}^{n} \\frac {\\frac {1}{a_n - a_{n-1}}}{\\frac {k^2}{a_k}}= \\frac {\\frac {1}{a_n - a_{n-1}}}{\\frac {1^2}{a_1}} +\n \\frac {\\frac {1}{a_n - a_{n-1}}}{\\frac {2^2}{a_2}} + \\dots + \\frac {\\frac {1}{a_n - a_{n-1}}}{\\frac {n^2}{a_n}}"
To show that left hand side equal or bigger then 1, it's suffices to show that at least one of
the summands bigger or equal to 1.
One can always choose such a summand.
Let it be :
"\\frac{\\frac{a}{b}}{\\frac{c}{d}}= \\frac{ad}{bc}"
"\\Downarrow"
"\\sum_{k=1}^{n} \\frac {na_k}{(a_1 - a_0)k^2}= \\frac {na_1}{(a_1 - a_0)1^2} +\n \\frac {na_2}{(a_1 - a_0)2^2} + \\dots + \\frac {na_n}{(a_1 - a_0)n^2} \\geq 1"
And again, it's enough to show that at least one of the summands bigger or equal to 1
for example first
where
Comments
Leave a comment